رِثَاءٌ ذو ثَلاثِ شُعَبٍ في شِعْرِ عَبْدِ الرَّحمنِ العشماوي: دِرَاسَةٌ أدَبِيَّةٌ تَحْلِيلِيَة = Ashmawi in his panegyric poems and the emotion of the poet as evident in the three trends of his panegyrics - Mohamed, Esameldien Dafalla (Department of Arabic Language and Literature, Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia (IIUM), 2011)
This paper intends to examine the trends of ‘Abdel Rahman al-‘Ashmawi in his panegyric poems and the emotion of the poet as evident in the three trends of his panegyrics. The poems were described and analyzed to reveal the purpose of the poet and the poetic characteristics for each of the three trends. For this reason, samples of the poet lamenting on the death of his mother and the death of a renowned scholar Syaikh ‘Abdel ‘Aziz bin Bazz and finally the death of a martyr Syaikh Ahmed Yasin; will be analyzed. The study concluded that his poems also highlighted on some social problems. The bitter and sad feeling were reflected strongly in the poems. The feeling of loyalty mixed with the feeling of surrendering to the destiny.